miR-489-3p Regulates the Oxidative Stress Response in the Liver and Gill Tissues of Hybrid Yellow Catfish (Pelteobagrus fulvidraco♀ × P. vachelli♂) Under Cu2+ Exposure by Targeting Cu/Zn-SOD - Qiang, Jun; Tao, Fanyi; Bao, Wenjin; He, Jie; Liang, Ming; Liang, Cong; Zhu, Haojun; Li, Xiahong; Chen, Deju; Xu, Pao (Frontiers in Physiology, 2019)
The copper/zinc superoxide dismutase (Cu/Zn-SOD) plays critical roles in protecting cells and tissues from oxidative damage. Excessive copper ions (Cu2+) in water can damage the cells of aquatic organisms, leading to impaired growth and development and reduced antioxidant defenses. Many regulatory factors control the response to excess Cu2+. microRNAs (miRNAs) are important small RNAs that regulate the expression of their target genes and participate in the oxidative stress response. In the present study, we used bioinformatics and dual luciferase reporter gene analyses to demonstrate that the miR-489-3p of hybrid yellow catfish (Pelteobagrus fuIvidraco♀×P. vachelli♂) binds to the 3'-untranslated region of its target gene, which encodes a Cu/Zn-SOD. The regulatory relationship between this miRNA and its target gene Cu/Zn-SOD was analyzed using qRT-PCR and luciferase activity assays. We also investigated the effect of the loss of miR-489-3p expression on the oxidative stress response in hybrid yellow catfish exposed to Cu2+. The results showed that the Cu/Zn-SOD 3′UTR region is fully complementary to positions 2–9 of the 5'-end seed region of miR-489-3p. There was a negative relationship between miR-489-3p expression levels and Cu/Zn-SOD expression. Silencing of miR-489-3p up-regulated Cu/Zn-SOD expression in the liver and gill tissues, increased activities of SOD and catalase, and reduced the malondialdehyde content. This study is the first to demonstrate that miR-489-3p targets Cu/Zn-SOD to mediate the oxidative response to metal stress. These findings provide a theoretical basis for further studies on the response to oxidative stress caused by metals in cultured fish, and provide an experimental basis for the management of the culture environment.